Evaluation of the Corrosion Erosion by Cavitation of Multilayer Coatings Type Binary, Ternary and Quaternary Deposited on Steel AISI 4140 (2014)
This article presents the evaluation of the corrosion erosion resistance erosion caused by cavitation generated on the binary type coatings [TiN / CrN]200, ternary [TiN / AlTiN]200 and quaternary [TiCN / TiNbCN]200 obtained by physical vapour deposition magnetron sputtering technique multi-target and deposited on 4140 steel substrates by comparing the uncoated substrate. The coatings were exposed to erosive, corrosive conditions and synergy compared to AISI 4140 steel. The electrochemical characterization are employed electrochemical impedance spectroscopy techniques and Tafel polarization curves. With respect to the characterization of degraded surfaces scanning electron microscope was used. The evaluation of the phenomenon of mechanical wear due to cavitation is performed using a high frequency generator. The protective effect in each of the evaluated systems was determined, generating improvements in the mechanical and corrosion properties.